(untitled) (Tempo e Argumento, 2023)
Cuban psychiatry experienced an important paradigm shift towards the beginning of the 1960s. In keeping with what was happening at the political, economic and other spheres of society, Cuban psychiatry adopted the Soviet model. From that perspective, a new mental hygiene policy was implemented, which had as its objectives not only the expansion and dissemination of psychiatric services, but also to normalize the population based on a citizen model in accordance with the socialist society that was beginning to be built. This article results from the analysis of the relationship between political discourse and that of mental hygiene in the context of the implementation of the Soviet model in Cuban psychiatry.